Intervensi Cognitive Restructuring dan Self-Instruction untuk Meningkatkan Self-Esteem Studi Kasus - Fitratul Khairat; Tatik Meiyuntariningsih (Jurnal Psikologi, 2025)
This study aimed to examine the effectiveness of cognitive restructuring, self-instruction, and parental psychoeducation in improving self-esteem in individuals with low self-esteem. The study employed a qualitative descriptive approach with a case study design involving one female subject in early adulthood. Data were collected through in-depth interviews, observations, personality tests, and self-esteem screening using the Rosenberg Self-Esteem Scale (RSES). The intervention was conducted offline over five sessions using cognitive restructuring, self-instruction training, role-play, and reflective discussion, followed by one session of parental psychoeducation. The effectiveness of the intervention was evaluated by comparing pre-test and post-test scores and observing cognitive and emotional changes during the intervention process. The results indicated a significant improvement in the subject’s self-esteem. The RSES score increased from 11 (low category) at pre-test to 25 (normal category) at post-test, reflecting a gain of 14 points, equivalent to 46.7% of the total possible score range (0–30). In addition to the quantitative improvement, qualitative findings showed a reduction in negative automatic thoughts, increased self-acceptance, and an improved ability to apply positive self-instructions in triggering situations. The subject also reported feeling calmer, more confident, and more capable of managing self-evaluative thoughts in daily activities. These findings suggest that the integration of cognitive restructuring, self-instruction, and parental psychoeducation is effective in enhancing self-esteem both cognitively and emotionally. This intervention model may serve as a practical approach for addressing low self-esteem in late adolescents and young adults.